2023
DOI: 10.34067/kid.0005082022
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Timing of De Novo Sepsis in Critically Ill Children after Acute Kidney Injury

Abstract: Background: Acute kidney injury (AKI) is common among critically ill children and is associated with an increased risk for de novo infection, however little is known about the epidemiology and temporal relationship between AKI and AKI-associated infection in this cohort. Methods: We conducted a single-center retrospective cohort study of children admitted to the pediatric and cardiac ICUs at a tertiary pediatric care center. The relationship between non-septic AKI and the development of hospital-acquired sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…5 After discharge, AKI survivors are at increased risk of developing chronic kidney disease (CKD), end-stage kidney disease, cardiovascular disease and death. 6 Other studies suggest that AKI predisposes to disparate sources of morbidity including infection, [7][8][9][10] bone fracture, 11 stroke, 12 gastrointestinal haemorrhage 13 and dementia. 14 While muscle wasting is well described in patients with CKD, 15 16 the contribution of AKI-RRT to muscle wasting in critically ill patients has not been previously studied.…”
Section: Open Accessmentioning
confidence: 99%
“…5 After discharge, AKI survivors are at increased risk of developing chronic kidney disease (CKD), end-stage kidney disease, cardiovascular disease and death. 6 Other studies suggest that AKI predisposes to disparate sources of morbidity including infection, [7][8][9][10] bone fracture, 11 stroke, 12 gastrointestinal haemorrhage 13 and dementia. 14 While muscle wasting is well described in patients with CKD, 15 16 the contribution of AKI-RRT to muscle wasting in critically ill patients has not been previously studied.…”
Section: Open Accessmentioning
confidence: 99%
“…In this issue of Kidney360 , Formeck and colleagues 8 fill this gap in knowledge by evaluating the temporal relationship of sepsis after an AKI event in 5695 children admitted to pediatric and cardiac intensive care units (ICU) at a tertiary care center between 2010 and 2014. AKI occurred in 20% ( N =1153) of children.…”
mentioning
confidence: 99%
“…The pediatric timeline for sepsis development post-AKI is similar to that reported in adults and neonates. 3 , 6 Formeck et al 8 found that sepsis occurred at a median of 2.6 (1.5–4.7) days post-AKI, with 80% developing sepsis within 7 days and 97% within 2 weeks of AKI. Significant risk factors for development of sepsis post-AKI included surgery before ICU admission, male sex, higher severity of illness scores within 24 hours of ICU admission, leukopenia, and the presence of an indwelling central line.…”
mentioning
confidence: 99%
See 2 more Smart Citations